2020
DOI: 10.20546/ijcmas.2020.906.466
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Weather Parameters on Incidence of Aphids, Myzus persicae Sulzeron Chilli in Andhra Pradesh, India

Abstract: To know the initial occurrence and subsequent build-up of aphids population on chilli crop in relation to weather parameters, the field experiments were carried out from 2010-2012 at Horticultural Research station, Lam, Guntur, Andhra Pradesh. Seasonal incidence of aphids was recorded from leaves and fruits at weekly intervals during the crop growth period. Based on the two years data, the results revealed that the infestation and severity of aphid population were highly influenced by weather parameters. In 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 2 publications
1
1
0
Order By: Relevance
“…The study revealed that the population of aphid in bell pepper was positively correlated with maximum and minimum temperature in summer crop, whereas negatively correlated with maximum and minimum relative humidity in autumn crop. Similar observations were also reported by Kumar et al (2019) and Pathipati et al (2020).…”
Section: Effects Of Abiotic Factors On Population Build-up Of Apterou...supporting
confidence: 92%
“…The study revealed that the population of aphid in bell pepper was positively correlated with maximum and minimum temperature in summer crop, whereas negatively correlated with maximum and minimum relative humidity in autumn crop. Similar observations were also reported by Kumar et al (2019) and Pathipati et al (2020).…”
Section: Effects Of Abiotic Factors On Population Build-up Of Apterou...supporting
confidence: 92%
“…According to Jovičić et al [13], there is a significant correlation between the total daily air temperatures (ideal or maximum) for aphid development and the number of aphid peaks. When the combined impact of meteorological factors and aphid incidence was calculated, it was shown that the weather parameters contributed to 62 to 74% of the change in incidence [14]. Several studies have explored the relationship between weather parameters and the abundance, distribution, and behavior of A. fabae in faba bean fields.…”
Section: Introductionmentioning
confidence: 99%